Enforcement of the Law in the Sociological Domain - Kharis Kayla; Sukarno Sukarno; Dimas Yogapangestu; Diky Dikrurahman; Deni Yusup Permana (Pusat Publikasi Nusantara, 2024)
The purpose of this study is to examine how law enforcement is applied in Indonesia's sociological context. The results of the investigation indicate that community involvement is necessary for the application of law enforcement in the sociological sphere. It is believed that the community's participation and involvement in law enforcement can be used as a controlling factor when making decisions about the appropriateness of punishment for lawbreakers. The community can play a major role in reducing the number of legal infractions and deviations from unlawful acts that have become sociological phenomena by actively participating in the monitoring, supervision, and evaluation of the law enforcement practices in this nation.